Optimizing a Multi-Component Intranasal Entamoeba Histolytica Vaccine Formulation Using a Design of Experiments Strategy - Abhyankar, Mayuresh M.; Orr, Mark T.; Kinsey, Robert; Sivananthan, Sandra; Nafziger, Andrew J.; Oakland, David N.; Young, Mary K.; Farr, Laura; Uddin, Md Jashim; Leslie, Jhansi L.; Burgess, Stacey L.; Liang, Hong; et al. (Frontiers in Immunology, 2021)
Amebiasis is a neglected tropical disease caused by Entamoeba histolytica. Although the disease burden varies geographically, amebiasis is estimated to account for some 55,000 deaths and millions of infections globally per year. Children and travelers are among the groups with the greatest risk of infection. There are currently no licensed vaccines for prevention of amebiasis, although key immune correlates for protection have been proposed from observational studies in humans. We previously described the development of a liposomal adjuvant formulation containing two synthetic TLR ligands (GLA and 3M-052) that enhanced antigen-specific fecal IgA, serum IgG2a, a mixed IFNγ and IL-17A cytokine profile from splenocytes, and protective efficacy following intranasal administration with the LecA antigen. By applying a statistical design of experiments (DOE) and desirability function approach, we now describe the optimization of the dose of each vaccine formulation component (LecA, GLA, 3M-052, and liposome) as well as the excipient composition (acyl chain length and saturation; PEGylated lipid:phospholipid ratio; and presence of antioxidant, tonicity, or viscosity agents) to maximize desired immunogenicity characteristics while maintaining physicochemical stability. This DOE/desirability index approach led to the identification of a lead candidate composition that demonstrated immune response durability and protective efficacy in the mouse model, as well as an assessment of the impact of each vaccine formulation component on protection. Thus, we demonstrate that both GLA and 3M-052 are required for statistically significant protective efficacy. We also show that immunogenicity and efficacy results differ in female vs male mice, and the differences appear to be at least partly associated with adjuvant formulation composition.